2,3-Dimethylphenyl benzoate - Hartmut Fuess; K. S. Babitha; Sabine Foro; B. Thimme Gowda (Acta Crystallographica Section E, 2008)
The structure of the title compound (23DMPBA), C15H14O2, resembles those of phenyl benzoate (PBA), 3-methylphenyl benzoate (3MePBA), 2,6-dichlorophenyl benzoate (26DCPBA) and other aryl benzoates, with similar bond parameters. The dihedral angle between the benzene and benzoyl rings in 23DMPBA is 87.36 (6)°, compared with values of 55.7° in PBA, 79.61 (6)° in 3MePBA and 75.75 (10)° in 26DCPBA. The molecules in 23DMPBA are packed into a chain-like structure in the direction of the a axis.